2022
DOI: 10.3390/bios12080616
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Holder for Awake Functional Imaging in Unanesthetized Mice: Applications in 31P Spectroscopy, Manganese-Enhanced Magnetic Resonance Imaging Studies, and Resting-State Functional Magnetic Resonance Imaging

Abstract: Anesthesia is often used in preclinical imaging studies that incorporate mouse or rat models. However, multiple reports indicate that anesthesia has significant physiological impacts. Thus, there has been great interest in performing imaging studies in awake, unanesthetized animals to obtain accurate results without the confounding physiological effects of anesthesia. Here, we describe a newly designed mouse holder that is interfaceable with existing MRI systems and enables awake in vivo mouse imaging. This ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Meanwhile, the release of Mn 2+ was determined by a MR spectrometer due to the paramagnetism of Mn 2+ , thus enabling sensitive tumor imaging by MRI. 53 As shown in Figure 3C,D, a negligible T1 MRI signal of Apt-EG@Dual/ hMNs was observed without GSH. However, after the addition of GSH, the T1 signal of Apt-EG@Dual/hMNs was significantly elevated and showed a high signal shadow in the T1 relaxation MRI mode.…”
Section: ■ Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Meanwhile, the release of Mn 2+ was determined by a MR spectrometer due to the paramagnetism of Mn 2+ , thus enabling sensitive tumor imaging by MRI. 53 As shown in Figure 3C,D, a negligible T1 MRI signal of Apt-EG@Dual/ hMNs was observed without GSH. However, after the addition of GSH, the T1 signal of Apt-EG@Dual/hMNs was significantly elevated and showed a high signal shadow in the T1 relaxation MRI mode.…”
Section: ■ Introductionmentioning
confidence: 76%
“…To verify this hypothesis, Dual/hMNs was incubated in PBS with different concentrations of GSH in the range of cancer cell GSH concentrations (1–10 mM) and showed that the fluorescence intensity gradually recovered with increasing concentration of GSH (Figures B and S4), suggesting that hMNs can be reduced by GSH and consequently release DNAzymes. Meanwhile, the release of Mn 2+ was determined by a MR spectrometer due to the paramagnetism of Mn 2+ , thus enabling sensitive tumor imaging by MRI . As shown in Figure C,D, a negligible T1 MRI signal of Apt-EG@Dual/hMNs was observed without GSH.…”
Section: Resultsmentioning
confidence: 99%
“…However, one significant challenge needs to be carefully considered, i.e., the potential stress caused to the animals during the imaging procedures, which can severely affect physiological states and brain hemodynamic activities. In previous studies, researchers have utilized various methods to measure stress levels in rodents, such as plasma corticosterone levels [2], changes in blood pressure, respiration rate or heat rate [7][8][9], etc. Though those measurements can be applied, it is still crucial to consider the limitations and potential confounding factors of each method when applying to the awake animals, particularly for awake fMRI protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The advancement of powerful in vivo imaging technology necessitates not only the development of more sensitive and specific imaging agents, but also more accurate detection and analysis methods. In this Special Issue, three reports focus on technical advancements [ 8 , 9 , 10 ]. These technical advances have led to enhanced in vivo imaging platforms that aid in the observation and quantification of intricate physiological and pathological changes.…”
mentioning
confidence: 99%
“…These technical advances have led to enhanced in vivo imaging platforms that aid in the observation and quantification of intricate physiological and pathological changes. Notably, the development of a holder that is suited to the functional and molecular imaging of awake mice provides more rigorous results than those obtained from anesthetized mice [ 9 ].…”
mentioning
confidence: 99%